HUBUNGAN SUPERVISI, KONDISI KERJA DAN PENGHASILAN DENGAN PRODUKTIVITAS DOKTER DALAM PENGISIAN DOKUMEN REKAM MEDIS DI RAWAT INAP RSUD UNGARAN KABUPATEN SEMARANG - Dina Septiyanita Pratiwi; Sutopo Patria Jati; Nurhasmadiar Nandini (Jurnal Kesehatan Masyarakat (Undip), 2020)
Medical Record is one indicator in determining the quality of health services in hospitals. However, filling medical records at Ungaran District Hospital has not yet reached the minimum service standard that has been set. This showed that the work productivity of doctors was still not optimal. In theory, supervision, work factors and contributions are extrinsic factors of motivation related to productivity. Thus, this study aimed to study the relationship between supervision, work requirements and assessment with the productivity of doctors in filling out medical record documents. This was quantitative research with cross-sectional study design. Questionnaires were given to 34 respondents with inclusion criteria of doctors who were directly involved with patients in the inpatient service. Data analyzed using univariate and bivariate analysis methods with the Chi-Square Test statistic. The results showed that 52.9% of respondents had low productivity. Based on statistical analysis test the independent variables include supervision (Pvalue = 0,000), working conditions (Pvalue = 0.041) and income (Pvalue= 0.005) showed the results that there was a relationship between supervision, working conditions and income with the productivity of doctors in filling out medical record documents. It is suggested to the hospital management to be able to improve the structure of the hospital and to provide a clear job description of the supervisor responsible for carrying out medical records filling by the doctor, improve the quality of printing medical record forms so that they are easy to read and to recalculate the proportion of income received by the doctor.